《虬髯客传》的古今诠释 : 以《虬髯客传》、《虬髯翁》和《风尘三侠之红拂女》为例 = Retelling “The legend of curled beard” : examples from Tang, Ming and Contemporary - 梁琇涵 Leong, Xiu Han (2015)
同样的题材放到不同的叙述家手中就会创造出不一样的作品。唐传奇《虬髯客传》从古至今以许多不同的文学类型呈现在我们眼前，从小说至话本 到现代电视剧，同样的题材不断被不同人诠释。本论文将会对比杜光庭的《虬髯客传》、凌蒙初的《虬髯翁》和现代电 视剧《风尘三侠之红拂女》，找出文本的差别，并分析不同文本类型和时代对 于同一个故事所起的影响。随着时代的改变，作品的主题不再一样，承载着故 事情节的人物也随着作品主题的改变而变化着。唐朝的传奇精简，明朝杂剧有了更多空间把人物发展的更圆满，现代电视剧为了拉长故事在唐传奇的基础上 加入更多人物和情节，人物剧情关系复杂化。时间和文学发展这两种调味料， 使千年前的故事到如今仍然有吸引力。唐朝的传奇述说着唐朝高宗的盛世霸业，因此塑造了一个与李世民旗鼓 相当的虬髯客，红拂女和李靖只是有着鲜明形象的配角，职位衬托李世民和虬髯客。明朝的杂剧除了以虬髯客为主也另有其他作品是以红拂女以及李靖为主 角，象征作家已发现风尘三侠中其他人物的特点与可造型，转而发展其他角色的形象。到了现代的电视剧中，配角红拂女和李靖竟然抢尽了风头，成为整个 作品的主角，与李世民平起平坐，反而虬髯客成了配角，这是因为电视剧为了 增加爱情的成分，而改变了人物的主次地位。Different works of literature could be borne from the same plot, as different writers breathe new lives in a story through their unique understanding and analysis of the story. “The legend of the Curled Beard”(Qiu Ran Ke Zhuan) is a Tang short story which has been adapted in to different plays and dramas by writers since it’s appearance, and its characters and plots have been retold in many different ways. In this thesis, we will be comparing “The Legend of the Curled Beard” with Ming dynasty play “The Man with the Curl Beard”(Qiu Ran Weng) and Television Drama “The Romance of Red Dust”(Feng Chen San Xia Zhi Hong Fu Nv) to analysis their difference and similarities, and to find out how different literature genres and different eras affect the presentation of the same story and characters. The Tang short story provides the base plot for all the other adaptations, portraying a majestic hero Curled Beard who is as wise as the second Tang Emperor Li Shi Min. The Ming play aims to persuade the rebels at that time to stop their rebellion by showing how the wise Curled Beard decide to expand his territory overseas and not overthrow the dynasty. However, the modern drama decided to change the protagonist to Red Dust, who had previously played a supporting role, as the plot focuses on the love story between Red Dust, her Husband Li Jing and Tang Emperor Li Shi Min. This research will attempt to find out the various factors that cause the change in plot and the way the story is retold, such as the objectives of the writers and the need of the audiences.